Designing Interactive, Contextual, and Technology-Based Disaster Mitigation Learning Materials to Improve Student Preparedness - Alfi, Muhammad; Yunita , Mirna; Monalisa (Corolla International Conference, 2025)
Disasters such as earthquakes, floods, and landslides often occur in Bengkulu; however, the level of preparedness among residents and children is still lacking. These findings are in line with research conducted in 2023 at educational institutions in Bengkulu City, which showed that students’ understanding was still inadequate. The lack of understanding and skills in disaster mitigation increases the risk of casualties and material losses. Therefore, the development of effective disaster mitigation learning materials in schools is important to build students’ awareness and ability to deal with disasters. This research aims to (1) identify the obstacles faced by teachers in delivering disaster mitigation materials in high schools in Bengkulu City, and (2) design interactive, contextual, and technology-based disaster mitigation learning materials to improve student preparedness. The research used the 4D method, which includes Define, Design, Develop, and Disseminate. For selecting participants, the study used purposive sampling based on the research requirements. The sample was taken from SMA 6 in Bengkulu City, which includes two classes, X and XI, making a total of 60 students. The findings showed a noticeable improvement in performance after using the learning module. The results of the student preparedness study at SMAN 6 Kota show that 65% of students are in the very prepared category, 18.9% of students are in the prepared category, and 13.6% of students are in the less prepared category. The learning module developed was proven to be valid with an average validation score of 3.50–3.80 (valid category).